Figurative insight and its development of prospective art pedagogues - Reinberga, Baiba; Garjāne, Beatrise (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The relevance of creativity (characteristics that describe the ability to formulate original and interesting thoughts, approaches, to form new material and spiritual values, to organise ideas and real happenings in unusual relations) becomes more and more important in the society these days, thus a pedagogue who is interested in creativity and is able to lead students towards the creative cooperation in the learning process is needed. How the competency of the perspective art subject teachers is formed in the study process? One of the criteria describing the professional readiness is the figurative perception ability and insight as the personal self-experience that is connected with the personal creative potential. The aim of the paper is to determine and describe the figurative insight and its development opportunities of the prospective art pedagogues. Their figurative insight and its potential development was revealed through the analysis of the correlation between in the results of integrated practical creative works (visual dominant creative text exercise) and results of creative potential describing test (Venker test). The findings allow stating the future course of the development of the perspective art pedagogues’ figurative insight